COMMUNICATIVE LANGUAGE TEACHING THROUGH SPEAKING ACTIVITIES DESIGNED IN A TEXTBOOK - Firiady, Maryska (LLT Journal: A Journal on Language and Language Teaching, 2018)
In pursuing the alignment between the goal of communication purpose and communicative approach, six new textbooks were designed to facilitate teaching-learning activities in Center of English for International Communication (CEIC) at Language Institute. Only an impressionistic overview was conducted as a pre-use evaluation due to limitation of time and resources. Thus, the writer attempted to do an in-depth pre-use evaluation of the recently revised textbook. This research aimed at investigating the activity variations and types of Communicative Language Teaching (CLT) activities presented in the revised textbook used for teaching Level 1 students. The speaking activities in the textbook were analyzed using Littlewoods (1981) theoretical framework on suggested communicative activities. The results showed that the textbook has various learning activities accommodating CLT activities, pre-communicative activities, structural activities, listening activities, vocabulary building activities, and reading activities. The CLT activities found in the textbook were differentiated between functional communication and social interaction activities. Functional communication activities specifically sharing information with restricted cooperation, in the form of class surveys and information gaps were dominant compared to other activities.